"Like Silkworms in Their Cocoons": Silkworm-Human Relations in Middle-Period Chinese Buddhism - Young, Stuart H. (History of religions, 2025)
This article is about how silkworms spun Buddhism in middle-period China (ca. third-tenth centuries CE). It traces the activities and influences of silkworms in Chinese Buddhist texts, which it treats as products of intrinsic entanglements among human and nonhuman agents. Throughout middle-period China, silk was the fabric of Buddhist monasticism. Silk enmeshed Buddhist monastery precincts, institutional economies, and modes of literary production. Chinese Buddhist texts were inscribed on silk; bound, wrapped, and tied in silk; and replete with discursive vestiges of silk and its other-than-human producers. This article shows how silkworms emerged through these sources as thinking, feeling, and moral subjects, as the kin of humans and deities, and as bodhisattvas themselves. It aims to foreground the many "small agencies" that contributed to building Chinese Buddhism from the ground up, literally: from the nutrients of the soil, through the leaves of trees and bodies of insects, to the halls of capital monasteries and doctrinal discourses of transmitted Buddhist texts. Silkworm caterpillars consumed mulberry leaves, secreted silk filaments, cocooned their bodies, transformed into pupae and moths, and were boiled to death in the cauldrons of human sericulture industry. Through these willful acts of consumptive production, silkworms embodied in form and function, and materialized in silk-spun cocoons, the central truths of the dharma. Silkworms did this through their intrinsic interrelations with human modes of sociomaterial production and samsaric existence. And in turn, human beings wove Buddhism in middle-period China, as with their material livelihoods, through the many small agencies of silkworm caterpillars.